Virtual exchange in Latin America: a profile of faculty and staff participants - Carmen King Ramírez (University of Groningen Press, 2022)
Latin American educational institutions report some of the lowest internationalization rates in the world (OECD, 2019). Historically, recognized barriers to internationalization have included programs based largely on student mobility as well as a lack of systematic implementation and funding (De Wit, Gacel-Ávila, & Knobel, 2017). In order to increase student and faculty access to international education experiences, Latin American universities are working to offer more inclusive, cost-effective methods of curricular diversification via Virtual Exchange (VE) (Lafont Castillo, Echeverría King, & Álvarez Ruíz, 2021). Given the limited publications currently available regarding VE in this region, this article seeks to establish a profile of Latin American faculty and staff who are presently engaged in VE initiatives as well as identify resources they need to ensure that VE programs are sustainable at their home institutions. The data presented in this article resulted from a mix-methods survey carried out among the Latin American Collaborative Online International Learning (LatAm COIL) network membership. These data provide important insights to the current trends and future possibilities for VE programs in this region.